Potential not pathology : helping your clients transform using ericksonian psychotherapy - J. Leslie, Paul; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
This book is designed to assist counsellors who would like to use and understand the psychotherapeutic strategies of Milton Erickson but often find it confusing, intimidating or unrealistic. Using colourful case studies and stories told in everyday language, this work will educate and help professionals in being able to understand how to adapt and apply creative and resourceful therapy interventions based on the concepts of Ericksonian psychotherapy. It will also assist clinicians and therapists in easily implementing the concepts of Ericksonian psychotherapy into their work in order to energise and revitalise their therapy sessions. Subjects explored include client resistance and client potential, the role of imagination and playfulness in the therapeutic work, and the healing possibilities hidden within stories and metaphors.
chapter 1 Developing the Erickson mindset -- chapter 2 Utilisation -- chapter 3 Altering patterns -- chapter 4 Multilevel communication -- chapter 5 The Renaissance man -- chapter 6 The possessed boy who belched.
Keywords: Hypnotism -- Therapeutic use; Psychotherapy; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine